The enclave of education from the approach of critical hermeneutics - Gracia Calandín, Javier; Tamarit López, Isabel (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
In this paper we adopt a critical stance, firstly, related to a view which seeks to explain the aims of education from the empirical research. Against this, we propose the hermeneutic-critical methodology to unravel what the ultimate goals of education are. We find that the approach of critical hermeneutics illuminates adequately education and provides a solvent ethical justification. Deeping on the critical dimension of hermeneutics, but without moving away from his experiential nerves, we notice that it is not enough to interpret the values set by society. It is necessary to delve into the ethical roots, which justify education as authentic human development of moral capabilities. This overriding experience of education, which is rooted in the human being, is a genuinely ethical experience. Regarding this, we emphasize eleven keys of the ethical hermeneutics and its advantages for the concretion of the enclave of the education.